Sosialisasi Pemanfaatan Aplikasi Mobile JKN pada Warga Desa Randu Gede Kabupaten Magetan - Budisaputro, Crismantoro; Apriliani, Eltigeka Devi; Windaningrum, Dewi (Pakis Journal Institute, 2025)
In 2017 BPJS launched the JKN mobile application which provides access to the registration process, membership information, contribution payments and health services. Based on the results of observations conducted by the team in this community service activity, it was found that in Randu Gede Village, Magetan Regency, there had been no information media related to the explanation of the use of the JKN mobile application such as posters, banners and the like. Public knowledge about the use of JKN mobile has not been widely distributed, villagers do not know the mechanism for using JKN mobile. The solution needed is the need for efforts to help the community to optimize the use of the JKN mobile application in accessing health services. The activities that can be carried out are in the form of socialization. Based on the results of the pre-test and post-test analysis, there was an increase in knowledge of the use of features on the JKN mobile application. The average knowledge of participants referring to the pre-test was 16% and increased with references from the post-test results of 83%.